Curriculum and Political Development: An Examination of High School Textbooks - S. M. Taheri; A. Darabi, Ph.D.; M. J. Haghshenas, Ph.D.; A. R. Soltani, Ph.D. (خانواده و پژوهش, 2022)
This study was undertaken to investigate how the components of political development derived from different theories, Holy Quran, hadith and the Constitution of the Islamic Republic of Iran were mirrored in high school curriculum. This applied research had a descriptive design. Content analysis was utilized in this study and the statistical population was comprised of all social studies, history, sociology, Persian literature, and Islamic education textbooks in junior and senior high school (32 textbooks in 2015-16 school year). The utilized technique was Shannon Entropy and the unit of analysis was pages, which included a total number of 4375 pages. Results indicated that: 1) The components related to political development were considered about 2174 times in the aforementioned textbooks, with the frequency of 250, 739, 94, 446, 341, and 304 for human dignity, eligibility, law-abiding, participation, competition, and critical thinking, respectively; 2) The findings show that participation component had the highest frequency and significance, while critical thinking was the least frequently covered topic in these books.